Isolation of Pigment Producing Actinomycetes from Lava Durian Planted Soil - Kabbua, Thai (Journal of Advanced Development in Engineering and Science, 2023)
The objectives of this study were to isolate pigment producing actinomycetes from lava durian planted soil and to study fiber dyeing with extracted dye. The actinomycetes were isolated from soil of lava durian garden in Phran subdistrict, Khunhan district, Sisaket province by using sodium caseinate agar (SCA) as the isolation medium. A total of 27 actinomycete isolates producing pigment-substrate mycelia were obtained in 4 color groups such as white, brown, yellow and pink. For dye production, the isolated actinomycetes were inoculated on broke-milled rice in solid state fermentation for 5-7 days. The inoculated broke-milled rice was dried and finely ground. Dye was extracted by using 70% ethanol. The extracted dye was obtained in pink and yellow. Cotton fibers were dyed with extracted dye from only 4 isolates. Isolate ALD1, ALD15 and ALD19 were pink, and isolate ALD27 was yellow. Morphological and biochemical test showed that all of 4 isolates were Streptomyces. However, the optimum conditions for fiber dyeing and color fastness testing should be further investigated to be applied in dye industry in the future.